2020
DOI: 10.1002/jbt.22512
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural, cytotoxic and pharmacokinetic evaluation of some thiosemicarbazone derivatives

Abstract: Iron(III) and nickel(II) complexes bearing a thiosemicarbazone framework were synthesized by a one‐pot synthesis method. The structures were characterized by elemental analysis, IR, 1H NMR, APCI Mass, conductivity, magnetic moment measurements. Molecular and crystal structures of the iron(III) complex were obtained from single‐crystal X‐ray diffraction. The findings showed that the metal atom adopts a slightly distorted square‐pyramidal coordination, with the four donor atoms of the thiosemicarbazone ligand de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[67] Two of them metabolized by cytochrome P450 (CYP) enzymes are cytotoxic in IC 50 values of 1.34-5.13 μM range against Caco2, HCT116, Hep3B, HepG2 cancerous cell lines from different origins. [68] Another analogous complex has been reported to exhibit usable cytotoxicity on HT-29 and HeLa cells in the 11-16 μM range of IC 50 by binding to DNA with 10 5 of intrinsic constant. [61] When the structure-activity relationship is evaluated, it was seen that the cytotoxic performances of Fe2, Fe5, and Fe8 having 4-OCH 3 group were superior to the others.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…[67] Two of them metabolized by cytochrome P450 (CYP) enzymes are cytotoxic in IC 50 values of 1.34-5.13 μM range against Caco2, HCT116, Hep3B, HepG2 cancerous cell lines from different origins. [68] Another analogous complex has been reported to exhibit usable cytotoxicity on HT-29 and HeLa cells in the 11-16 μM range of IC 50 by binding to DNA with 10 5 of intrinsic constant. [61] When the structure-activity relationship is evaluated, it was seen that the cytotoxic performances of Fe2, Fe5, and Fe8 having 4-OCH 3 group were superior to the others.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…The biological versatility of thiosemicarbazones as antimalarial, antibacterial, anticancer, antifungal, antitumor, and urease inhibitor made them multifaceted and potent agents. [10][11][12][13][14][15][16][17][18] It was also observed that different series of molecular structures showing close homology with urea/thiourea moiety, such as the (thio)semicarbazones, [19,20] N-phenyl thiosemicarbazones, [21] hydrazones [22] led to urease inhibitory activity. [23] The structure of some of the reported thiosemicarbazone derivatives as urease inhibitors is presented in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…Thiosemicarbazone family are interesting molecules from a medicinal chemistry viewpoint because of their broad range of biological activities. The biological versatility of thiosemicarbazones as antimalarial, antibacterial, anticancer, antifungal, antitumor, and urease inhibitor made them multifaceted and potent agents [10–18] . It was also observed that different series of molecular structures showing close homology with urea/thiourea moiety, such as the (thio)semicarbazones, [19,20] N‐phenyl thiosemicarbazones, [21] hydrazones [22] led to urease inhibitory activity [23] .…”
Section: Introductionmentioning
confidence: 99%